Analisis Tingkat Kepatuhan Minum Obat terhadap Kejadian Kekambuhan pada Pasien Gastroesophageal Reflux Disease (GERD) - Rasyid, M. Gazali Abdul; Indriani, Nurul; Kresnapati, I Nyoman Bagus Aji (Department of Pharmacy, Bumigora University, 2025)
: Gastroesophageal Reflux Disease (GERD) is a digestive tract disorder with a rising prevalence both globally and in Indonesia. Recurrence among GERD patients is often linked to medication adherence. This study aims to analyze the relationship between medication adherence and recurrence in GERD patients at RSUD Tanjung in 2024. A qualitative method was used, with data collected from medical records of patients undergoing regular treatment. A total of 84 patients were selected using Slovin's formula from a population of 538 patients. Data were analyzed descriptively and followed by Chi-Square, Homogeneity, and ANOVA tests. The results showed that the recurrence rate among GERD patients was 66%, while the medication adherence rate was only 34%. The Chi-Square test showed no significant relationship between gender and visit frequency. The Homogeneity test indicated that the data variances among groups were homogeneous, and the ANOVA test showed a significant difference based on visit frequency. The study concludes that medication adherence among GERD patients at RSUD Tanjung remains low, contributing to a high recurrence rate. Educational and interventional efforts are needed to improve patient adherence to therapy in order to reduce GERD recurrence rates.